Critical minds in Arabic and Islamic studies courses: A whiff of change - Al Kuhayli, Halah A. (Teaching theology and religion, 2021)
In the present manuscript, we report the findings of a study that surveyed female college students' views of revamped Islamic and Arabic Culture courses embedded in the curriculum of a secular academic program in the Kingdom of Saudi Arabia. Of interest were students' views of and responses to recently implemented features of the curriculum and instruction that exemplified active learning. The ancillary aim was to determine whether views and responses were linked to performance. At the end of the semester, students recognized that the courses' curriculum and instruction fostered active learning opportunities, and expressed an appreciation for learning that is impactful. Results involving performance were mixed though. In fact, whereas recitation and final test performance decreased with students' recognition that instruction prioritized understanding of facts and ideas, greater discussion of matters that engaged students' attention, such as cognitive distortions and personal views, was associated with higher midterm and final test performance. It was concluded that the novelty of activities capable of engaging students in the learning process might explain students' appreciation of active learning as well as such activities' mixed relationship with performance outcomes.